Answer:(-2,3.5)
Step-by-step explanation: Add the endpoints and divide by two for the x-values and the y-values
Answer:
We conclude that:
Step-by-step explanation:
Given:
![-\left(9x\right)^0](https://tex.z-dn.net/?f=-%5Cleft%289x%5Cright%29%5E0)
To determine:
Explain how to solve the expression
<u>Solving the expression</u>
![-\left(9x\right)^0](https://tex.z-dn.net/?f=-%5Cleft%289x%5Cright%29%5E0)
Apply the exponent rule
![a^0=1,\:\quad \:a\ne \:0](https://tex.z-dn.net/?f=a%5E0%3D1%2C%5C%3A%5Cquad%20%5C%3Aa%5Cne%20%5C%3A0)
so the expression becomes
![-\left(9x\right)^0\:=\:-1](https://tex.z-dn.net/?f=-%5Cleft%289x%5Cright%29%5E0%5C%3A%3D%5C%3A-1)
Therefore, we conclude that:
Answer:
12.68 de
Step-by-step explanation:
Let's solve this by creating an equation.
Let X = the second factor
![X\times90=7000\\X = 7000\div90\\X= 77.77777](https://tex.z-dn.net/?f=X%5Ctimes90%3D7000%5C%5CX%20%3D%207000%5Cdiv90%5C%5CX%3D%2077.77777)